Engines of creation - Drexler, K. Eric (London : Fourth Estate, 1996)
From the Publisher: This brilliant work heralds the new age of nanotechnology, which will give us thorough and inexpensive control of the structure of matter. Drexler examines the enormous implications of these developments for medicine, the economy, and the environment, and makes astounding yet well-founded projections for the future.
Foreword / Marvin Minsky -- Acknowledgments -- Part 1: Foundations Of Foresight -- 1: Engines of construction -- 2: Principles of change -- 3: Predicting and projecting -- Part 2: Profiles Of The Possible -- 4: Engines of abundance -- 5: Thinking machines -- 6: World beyond earth -- 7: Engines of healing -- 8: Long life in a open world -- 9: Door to the future -- 10: Limits to growth -- Part 3: Dangers And Hopes -- 11: Engines of destruction -- 12: Strategies and survival -- 13: Finding the facts -- 14: Network of knowledge -- 15: Worlds enough, and time -- Afterword -- Notes and references -- Glossary -- Index.
Includes bibliographical references : (page [243]-283) and index.
Keywords: High technology; Twentieth century -- Forecasts